2016
DOI: 10.1210/en.2015-1629
|View full text |Cite
|
Sign up to set email alerts
|

Nonnuclear Estrogen Receptor Activation Improves Hepatic Steatosis in Female Mice

Abstract: Estrogens have the potential to afford atheroprotection, to prevent excess adiposity and its metabolic complications including insulin resistance, and to lessen hepatic steatosis. Cellular responses to estrogens occur through gene regulation by nuclear estrogen receptors (ERs), and through signal initiation by plasma membrane-associated ER. Leveraging the potentially favorable cardiometabolic actions of estrogens has been challenging, because their reproductive tract and cancer-promoting effects adversely impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 67 publications
1
24
0
1
Order By: Relevance
“…Contrary to their stimulatory action on reendothelialization and on NO production,22, 23 none of these molecules was able to prevent atheroma LDLr −/− mice. Interestingly, a similar finding was previously reported in EDC‐treated apolipoprotein E–deficient mice 68. Accordingly, we previously showed that 17β‐estradiol failed to induce any atheroprotective action using mouse model in which nuclear effects are abrogated (ERα‐AF20/LDLr −/− mice), highlighting the requirement of nuclear/transcriptional actions of ERα for early atheroprotection at the level of the aortic sinus 32.…”
Section: Discussionsupporting
confidence: 85%
“…Contrary to their stimulatory action on reendothelialization and on NO production,22, 23 none of these molecules was able to prevent atheroma LDLr −/− mice. Interestingly, a similar finding was previously reported in EDC‐treated apolipoprotein E–deficient mice 68. Accordingly, we previously showed that 17β‐estradiol failed to induce any atheroprotective action using mouse model in which nuclear effects are abrogated (ERα‐AF20/LDLr −/− mice), highlighting the requirement of nuclear/transcriptional actions of ERα for early atheroprotection at the level of the aortic sinus 32.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, a chemical model of menopause created by administration of 4-vinylcyclohexene diepoxide (VCD), which depletes primordial follicles, creates insulin resistance, fatty liver and dyslipidemia (Romero-Aleshire et al 2009). In addition to estrogen deficiency causing steatosis in rodent models, estrogen replacement reduces steatosis (Barrera et al 2014; Bryzgalova et al 2008; Villa et al 2012; Camporez et al 2013; Chambliss et al 2016; Palmisano et al 2016; Wang et al 2015; Zhu et al 2013; Kim et al 2014). …”
Section: Lack Of Estrogen Signaling Promotes Liver Tg Accumulation Anmentioning
confidence: 99%
“…An estrogen dendrimer conjugate (EDC) comprised of estradiol (E2) molecules linked to a poly(amido)amine dendrimer selectively activates nonnuclear ER, and in mice. This EDC compound does not have activity to promote uterus growth and does not promote breast cancer growth, but does blunt liver fat accumulation with obesity, suggesting that the non-nuclear effects of estrogen are critical with regard to regulation of hepatic fat content (Chambliss et al 2016; Chambliss et al 2010). Interesting targeting non-nuclear estrogen with EDC did not prevent atherosclerosis in apoE null mice, which estradiol did (Chambliss et al 2016).…”
Section: Selective Estrogen Delivery Approaches and Liver Lipid Metabmentioning
confidence: 99%
“…Concentrations of plasma CRP, SAP, total IgG or IgG subclasses in mice were measured using ELISA reagents from Life Diagnostics, Immunology Consultants Laboratory Inc., ZeptoMetrix Corporation, and Bethyl Laboratories, respectively. Plasma triglycerides were measured by colorimetric enzymatic assay, and plasma free fatty acids were quantified using the VITROS 250 Chemistry System as previously described (43). Evaluation of body composition, food consumption, and energy expenditure.…”
Section: Figure 5 Igg From Hfd-fed Mice Attenuates Insulin-induced Ementioning
confidence: 99%